Fiqh Al-Bai's Review of Online Buying and Selling in Special Groups on Facebook Platform - Meirani, Nadia; Komalasari, Retno (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2022)
Online buying and selling activities on the Facebook platform specifically for residents of Grand Cikarang City housing under the name of the Online Market group